The “Public Philosophy” of Organizations - Reimann, Bernard C. (Academy of Management Journal, 1974)
A new instrument for measuring the beliefs, attitudes, or values held by the management of a firm with respect to its various publics is used in a field study of managers in 19 firms. This instrument is effective in differentiating between the management teams in different kinds of business organizations.